New Record Marsdenia tenacissima (Asclepiadoideae, Apocynaceae) In Gunung Ijo Baturagung Yogyakarta - Widodo Widodo; Muhammad Ja'far Luthfi (Biology, Medicine, & Natural Product Chemistry, 2016)
Marsdenia tenacissima population were found among wild bushes at S 07 o 47’ 03.4”; E 110o 30’ 48.0” about 415 meter above sea level in Gunung Ijo Baturagung Yogyakarta. Identification was based on literature and herbarium specimen. The research was conduct using exploration methods, morphoanatomical observation, and specimen collection. Marsdenia tenacissima in Jawa was not reported in Flora of Java. Marsdenia tenacissima habitus was liana. The specific character for its identification was pollinia’s structure. This paper presented other important character namely leaf, stem, flower, pollinia, and fruit of Marsdenia tenacissima in Gunung Ijo Baturagung Yogyakarta. Accurate description and examination of any plant species were needed for its conservation and awareness of public to local biodiversity.